2016
DOI: 10.1371/journal.pone.0158916
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy and Cardiac Death in Long-Term Survivors of Esophageal Cancer: An Analysis of the Surveillance, Epidemiology, and End Result Database

Abstract: ObjectiveRadiation therapy (RT) for esophageal cancer often results in unintended radiation doses delivered to the heart owing to anatomic proximity. Using the Surveillance, Epidemiology, and End Results (SEER) database, we examined late cardiac death in survivors of esophageal cancer that had or had not received RT.Methods5,630 patients were identified that were diagnosed with esophageal squamous cell carcinoma (SCC) or adenocarcinoma (AC) from 1973–2012, who were followed for at least 5 years after therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
(41 reference statements)
3
37
0
2
Order By: Relevance
“…This is consistent with a retrospective single-institution report of HD therapy being associated with more acute adverse effects and potentially suboptimal surgical conditions (23). Nevertheless, in light of studies demonstrating that advanced RT techniques may decrease adverse and postoperative events, further work must assess whether a decrease in dose has additive effects as well (24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with a retrospective single-institution report of HD therapy being associated with more acute adverse effects and potentially suboptimal surgical conditions (23). Nevertheless, in light of studies demonstrating that advanced RT techniques may decrease adverse and postoperative events, further work must assess whether a decrease in dose has additive effects as well (24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 83%
“…Since radiotherapy is an important component in the management of EC, the delivery of radiotherapy is an important consideration given the critical organs of the heart and lung that surround tumors in the mid to distal esophagus [20]. Radiotherapy in this area delivers a significant dose to the surrounding organs, and therefore advanced techniques to reduce the dose exposure of these organs will mitigate the toxicities and improve outcomes for patients.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The long‐term results of Radiation Therapy Oncology Group (RTOG) clinical trial 85‐01 confirmed that chemoradiation increased overall survival for patients with esophageal carcinoma compared with radiotherapy (RT) alone . Due to proximity to surrounding organs at risk (OAR) such as heart, spinal cord, lungs, kidney, liver, and the remaining stomach, the RT planning for distal esophagus carcinoma poses special challenges . Sufficient radiation doses must be applied to the tumor and lymph node areas, while protecting nearby critical normal structures.…”
Section: Introductionmentioning
confidence: 99%